Effects of Hypoxia and Chitosan on Equine Umbilical Cord-Derived Mesenchymal Stem Cells - D. J. Griffon; J. Cho; J. R. Wagner; C. Charavaryamath; J. Wei; A. Wagoner Johnson (Stem Cells International)
Chitosan opens new perspectives in regenerative medicine as it enhances the properties of mesenchymal stem cells (MSCs) through formation of spheroids. Hypoxia has also been proposed to enhance stemness and survival of MSCs after in vivo implantation. These characteristics are relevant to the development of an off-the-shelf source of allogenic cells for regenerative therapy of tendinopathies. Umbilical cord-derived MSCs (UCM-MSCs) offer an abundant source of immature and immunoprivileged stem cells. In this study, equine UCM-MSCs (eqUCM-MSCs) conditioned for 3 and 7 days on chitosan films at 5% oxygen were compared to eqUCM-MSCs under standard conditions. Equine UCM-MSCs formed spheroids on chitosan but yielded 72% less DNA than standard eqUCM-MSCs. Expression of Sox2, Oct4, and Nanog was 4 to 10 times greater in conditioned cells at day 7. Fluorescence-labeled cells cultured for 7 days under standard conditions or on chitosan films under hypoxia were compared in a bilateral patellar tendon defect model in rats. Fluorescence was present in all treated tendons, but the modulus of elasticity under tension was greater in tendons treated with conditioned cells. Chitosan and hypoxia affected cell yield but improved the stemness of eqUCM-MSCs and their contribution to the healing of tissues. Given the abundance of allogenic cells, these properties are highly relevant to clinical applications and outweigh the negative impact on cell proliferation.